Strigolactones Modulate Cellular Antioxidant Defense Mechanisms to Mitigate Arsenate Toxicity in Rice Shoots - Mohammad Golam Mostofa (MDPI AG, 2021)
Metalloid contamination, such as arsenic poisoning, poses a significant environmental problem, reducing plant productivity and putting human health at risk. Phytohormones are known to regulate arsenic stress; however, the function of strigolactones (SLs) in arsenic stress tolerance in rice is rarely investigated. Here, we investigated shoot responses of wild-type (WT) and SL-deficient d10 and d17 rice mutants under arsenate stress to elucidate SLs’ roles in rice adaptation to arsenic. Under arsenate stress, the d10 and d17 mutants displayed severe growth abnormalities, including phenotypic aberrations, chlorosis and biomass loss, relative to WT. Arsenate stress activated the SL-biosynthetic pathway by enhancing the expression of SL-biosynthetic genes D10 and D17 in WT shoots. No differences in arsenic levels between WT and SL-biosynthetic mutants were found from Inductively Coupled Plasma-Mass Spectrometry analysis, demonstrating that the greater growth defects of mutant plants did not result from accumulated arsenic in shoots. The d10 and d17 plants had higher levels of reactive oxygen species, water loss, electrolyte leakage and membrane damage but lower activities of superoxide dismutase, ascorbate peroxidase, glutathione peroxidase and glutathione S-transferase than did the WT, implying that arsenate caused substantial oxidative stress in the SL mutants. Furthermore, WT plants had higher glutathione (GSH) contents and transcript levels of OsGSH1, OsGSH2, OsPCS1 and OsABCC1 in their shoots, indicating an upregulation of GSH-assisted arsenic sequestration into vacuoles. We conclude that arsenate stress activated SL biosynthesis, which led to enhanced arsenate tolerance through the stimulation of cellular antioxidant defense systems and vacuolar sequestration of arsenic, suggesting a novel role for SLs in rice adaptation to arsenic stress. Our findings have significant implications in the development of arsenic-resistant rice varieties for safe and sustainable rice production in arsenic-polluted soils.